Superwoman as a transitional link in the understanding of corporality (Reflections on the discourse of modernity and postmodernity) - Borakovska, Maria Oleksandrivna (NTU "KhPI", 2017)
Each change of the human being meets a certain transformation of the human body, changing its physical and sensual components. Human nature, which is divided into male and female, creates a theory of moral and identification. The image of Superwoman that becomes an option for understanding the modern woman appears as a claim to identity, as imposed image that challenges modern woman to identify herself. Breaking of the paradigm of consciousness actualizes the theme of physicality, the heuristic potential of which is unexplored. Images of superwoman and superman which are implemented in the mass-media give the opportunity to understand the modern representation of physicality. This gives us the opportunity to highlight the features and direction of these representations in different film dimensions.

Розлом парадигми свідомості актуалізує тему тілесності, евристичний потенціал якої малодосліджений. Розпорошення дискурсів про концепт тіла висвітлює недостатність його філософського осмислення, а також певні недоліки концептуалізації і незначної методологічної впевненості. Образи супервумен і супермен, які реалізуються в мас-медіа, дають можливість зрозуміти сучасну репрезентацію тілесності. Це дає нам можливість виокремити особливості і напрямки цих репрезентацій у різних вимірах кіно.
Superwoman як перехідна ланка у розумінні тілесності (Роздуми над дискурсом модерну і постмодерну)
Keywords: mass-media; dimension; cinema; visualization; мас-медіа; вимір; кіно; візуалізація